Virtual colonoscopy: CT and MR colonoscopy – How good is it? - Kumar, Gnana (Malaysian Medical Association, 2005)
SUMMARY: Since its introduction in 1994 Virtual Colonoscopy (CT/MR Colonography) has continued to improve considerably. This is as a result of vastly of vastly superior and faster multidetector computed tomography scanners and quicker MR scanners. Improvements in software and hardware of computers allow the dynamic and interactive real time viewing of the colon in 2 and 3 dimensional images.